Vous êtes sur la page 1sur 61

2

3

n

 

n

 

 

 

 

 

R C

a

a

11

21

a m1

a

a

12

22

a m2

.

.

.

.

.

.

a

a

1n

2n

a

mn

a ij

m n (m, n)

(a ij )

O =

0

0

0

0

0

0

.

.

.

.

.

.

.

.

.

0

0

0

(a 1 ,

, a n )

b

b

1

2

b

m

i

I AI = IA = A A

I

(a ij ) (b ij )

a ij = b ij i, j

(a ij ) a ij

=

=

0

i

j

a ii

=

1

(m, n) (a ij ) (b ij )

, m

(c ij ) (m, n) c ij = a ij + b ij i = 1,

j = 1,

,

n

A = 4

0

B =

1

3

5

2

3

2

6

1

3 B =

2

5

3

1

1

0

0 A +

A, B C (m, n)

A + B = B + A

(A + B) + C = A + (B + C)

A + O = O + A = A O

A + (A) = O A = (a ij )

A = (a ij ) λ

λA =

λa

λa

11

21

λa m1

λa

λa

12

22

λa m2

.

.

.

.

.

.

.

.

.

λa

λa

1n

2n

λa mn

=

(λa ij )

A = (2 7 8) 3A = (6 21 24)

A, B (m, n)

λ(A + B) = λA + λB

(λ + µ)A = λA + µA

λ(µA) = (λµ)A

1A = A

= (b kl )

(r, p) AB n = r

A

= (a ij ) (m, n) B

C = (c il ) (m, p) c il =

j=n

a ij b jl

j=1

A = 3

0

AB

=

=

2

4

1

6 B = 5

6

1

0

3

4

2

1

2

3(1) + 2(5) + (1)(6) 0(1) + 4(5) + 6(6)

7

56

2

36

6

16

3(0) + 2(3) + (1)(4) 0(0) + 4(3) + 6(4)

3(2) + 2(1) + (1)(2) 0(2) + 4(1) + 6(2)

λ(AB) = (λA)B λ

A(BC) = (AB)C

(A + B)C = AC + BC

C(A + B) = CA + CB

AB

= BA

AB = O

A = O B = O

A B AB = BA =

I

A =

1

0

0

0

1

2

BA = 0

1

A =

B =

B = 0 0

0

0

0

1

2

0 1 AB = 0

0

0 1

0

1

= O B = 1

1

1

1

= O

AB = 0

0

0 0 = O

a 11

  a 22

 

.

.

0

0

0

.

i

= j

 

a 11

0

0

a

.

22

.

.

.

0

.

.

0

.

.

.

0

0

a nn

0 a nn

 

a ij = 0

a 11

0

a 22

.

.

.

a

0

0

nn

a ij = 0 i > j

a ij = 0 i < j

AA A 2 A 3 = A 2 A

A

t A

A = (a ij ) t A = (b ij ) b ij = a ji t ( t A) = A

1

A =   2

3

4

5 t A =

6

1

4

2

5

3

6

A A

A

R j ←− R j + kR i

A

R i ←− kR i

A R i ←→ R j

e e(A)

e A

E e I

E = e(I) E

e

3

L 2 L 3

L 2 6L 2

L 3 4L 1 + L 3

1

E 1 = 0

0

0

0

1

0

1

0

1

E 2 = 0

0

0

6

0

0

0 E 3 =

1

1

0

4

0

1

0

0

0

1

e E

m e(A) = EA A

(m, n)

R i R j

R i kR i R i

1

k R i

R j kR i +R j R j kR i +R j

e

e E E E

E

A A A

1

A =   2

4

0 2

1

1

3

8

A

A

1

2

4

0

1

1

−−−−−−→

L

3

+L

2

2

3

8

1

0

0

1

0

0

0

1

0

0

1

0

2

1

1

0

0

1

L 3 4L 1

−−−−−−→

L

2 2L 1

1

0

0

0

1

1

1

2

6

0

1

1

0

0

1

L 2 L 3

−−−−−→

L 1 +2L 3

2

1

0

1

2

4

0

1

0

0

0

1

1

0

0

0

1

0

0

0

1

A 1 =

11

4

6

11

4

6

2

0

1

2

0

1

2

1

1

1

2

1

L 3

−−→

L 2

1

0

0

0

1

0

0

0

1

11

4

6

2

0

1

2

1

1

A 1 = BC

1

C = 0

0

1

B =   0

0

1

0

0

0

1

0

0

1

0

0

1

0

0

1

1

0

1

0

0

1

0

0

0

1 0

1

0

2

0

1

0

1

0

0

0

1

0

0

1

0

1 0

1

0

0

1

0

4

0

1

0

2

0

1

0

1

0

2

a

a

11

21

a

a

12

22

2 A =

a 11

a

21

a a 22 detA =

12

a

a

11

21

a

a

12

22

= a 11 a 22 a 12 a 21

1

2

3

4

= 4 6 = 2

2

1

4

3

= 6 4 = 2

3 1

4 2

= 6 4 = 2

1

A

=

1 4 t A = 3
2

1

3

2

4 detA =

det t A

3

A =

a

a

a

11

21

31

a

a

a

12

22

32

a

a

a

13

23

33

detA

=

a

a

11

21

a 31

a

a

12

22

a 32

a

a

13

23

a 33

= a 11

a 11

a 22

a 32

a 23

a 33

detA =

1 3

6

0

2

1

0

4 2

= 1

6

0

a 12

a

a

13

23

a 12

a 32

a 13

a 33

a 21

4

2

+a 31

a 22

a 21

a 31

2

1

= 12 12 12 = 12

3

0

0

2

3

6 4

0

(1) i+k

2 i eme`

detA i eme`

k eme`

k eme`

a 22 (1) 2+2

a

a

11

31

a

a

13

33

 

+

+

(1) i+j

+

+

+

(1)

detA = a 11 C 11 +a 21 C 21 +a 31 C 31 C i1 a i1 detA

A detA

detA = a 21

a

a

12

32

a

a

13

33

+ a 22

a

a

11

31

a

a

13

33

a 23

a

a

11

31

a

a

12

32

k k

6

0

3

1

2

0

2 2 4 2

0

=

1

1 1

1 1

0

1

6

= 12

2(1)

1

1

1 1

1 1

0

1

3

2(3)

0

0

1 1

2(2)

0

2

= 12

=

2

1 3

1 3

0

1

0

2 2

=

2

1 3(1)

1 3(1)

3(0)

1

0

2 2

=

a 1 + d 1 b 1 c 1

2

a 2 + d 2

b

2

c

a 3 + d 3 b 3 c 3

=

a

a 2 b 2 c 2

b 1 c 1

1

a 3 b 3 c 3

+

d 1 b 1 c 1

d 2 b 2 c 2

d 3 b 3 c 3

1

1

1

2

2

2

2

3 1

= 0

1

1

=

0

1

0

1

1

C 1 +C 3

−−−−−−→

1

1

2

1 1

1

0 0

0

1 = 1

1

C

1 +C 3

−−−−→ C 3 C 1

3

2

6

3

1

1

2

7

6

3

1

2

4 3

1

2

7

2

4 3

C 1 +C 2 C 3

−−−−−−→

=

0

5

0

1

2

7

2

4 3

= 5

1

2

2

4

= 5(4 + 4) = 0

λ

λ

1

2

2

3

−−−−→

2L 1 L 2

0

1

2

3

= 2

1

2

2

3

= 1

n

a 1n

a

a

2n

nn

a a a

n = 1 a 11

n 2

11

21

n1

a

a

a

12

22

n2

.

.

.

.

.

.

n

a a a

11

21

n1

a 12

a 22

a n2

.

.

.

.

.

.

.

.

.

a 1n

a 2n

a nn

=

=

a i